Gamification in Management Education: Enhancing MBA Student Engagement and Performance through Game Based Learning Technologies - Rohit Mohite; Ravi Chaurasiya; Kiran Rodrigus; Anand Rajawat; Sandeep Sharma (CV. Pusdikra Mitra Jaya, 2025)
This study explores the integration of game-based learning technologies within management education to evaluate their influence on student engagement, motivation, and academic performance. The primary purpose is to assess whether gamification can enhance the learning experience for postgraduate business students by replicating real-world challenges in an interactive environment. A mixed-methods research design was adopted, involving surveys, classroom observations, and academic performance data from 150 MBA students across five Indian business schools. Game-based tools such as simulations, point systems, digital quizzes, and interactive role-play were implemented in subjects including marketing, operations, and strategic management. Quantitative analysis revealed that students exposed to gamified instruction demonstrated improved motivation levels, higher participation rates, and a statistically significant increase in academic scores. Qualitative feedback from focus group discussions further emphasized students’ preference for engaging, challenge-based activities over traditional lectures. The study concludes that gamification fosters active learning, improves conceptual understanding, and contributes to better classroom dynamics. However, it also highlights the need for thoughtful implementation, faculty training, and technological support. It is recommended that management institutes gradually incorporate structured gamified modules aligned with course outcomes and industry applications. Additional data collected includes comparative test scores, student satisfaction ratings, and faculty observations, which support the positive impact of gamification. The findings provide actionable insights for educators, curriculum designers, and academic administrators aiming to modernize MBA pedagogy through technology-enhanced strategies.